Tadeusz Buksiński’s Project of Transcendental Metapolitics and Confucian Political Philosophy: A Comparative Study - Rogacz, Dawid (Sensus Historiae, 2022)
The paper compares the idea of transcendental metapolitics as developed by Tadeusz Buksiński with the main assumptions of the Confucian political philosophy. The analysis is particularly focused on the ideals of good life, normative concepts of man, and understanding of the public sphere, relevant to these two axiologies of politics.